2014
DOI: 10.3109/1547691x.2014.945667
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ: A player on multiple fronts in the tumor microenvironment

Abstract: The physiological functions of transforming growth factor (TGF)-in cell signaling include regulation of developmental processes and cell growth. Tumor cells very often display altered regulation of the TGF signaling pathway, either by defects in TGF itself or in downstream components of the pathway. TGF can play a dual role in tumorigenesis, i.e. it can be either tumor-suppressive or tumor-promoting. TGF suppresses the growth of tumor cells; however, in advanced tumors, it is associated with induction of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 108 publications
0
42
0
1
Order By: Relevance
“…A previous study demonstrated that TGFβ expression in tumor cells is promoted by surrounding cells in the tumor microenvironment [28]. It has been reported that TGF-β1 was overexpressed in several cancers such as hepatocellular carcinoma and it was related to the progression of tumor cells [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that TGFβ expression in tumor cells is promoted by surrounding cells in the tumor microenvironment [28]. It has been reported that TGF-β1 was overexpressed in several cancers such as hepatocellular carcinoma and it was related to the progression of tumor cells [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…TGF- β regulates proliferation, differentiation, and functions of immune cells that include macrophages, dendritic cells, natural killer cells, B cells, and T cells. TGF- β also modulates innate and adaptive immunity (reviewed by Caja and Vannucci 85 ). The role of TGF- β in the regulation of T-cell maturation, proliferation, and expansion is particularly relevant to cancer progression.…”
Section: Antitumor Immunitymentioning
confidence: 99%
“…Основная функция TGF-b в большинстве клеток и тканей связана с контролем пролиферации и дифференцировки [92][93][94][95]. В нормальных эпителиальных клетках, а также на ранних стадиях опухолевой прогрессии (в премалигнизированных или хорошо дифференцированных раковых клетках) TGF-b действует как антипролиферативный фактор, угнетая канцерогенез, инвазивные и метастатические процессы [95,96]. Однако на поздних стадиях рака он поддерживает рост опухолей и метастазирование [92][93][94][97][98][99][100][101].…”
Section: трансформирующий фактор роста бета (Tgf-b)unclassified